Severe Hypoglycemia Caused by a Giant Borderline Phyllodes Tumor of the Breast: A Case Report and Literature Review - Liu, Yaoxia; Zhang, Min; Yang, Xudan; Zhang, Min; Fan, Zhen; Li, Yi; Wang, Tao; Chen, Ping (Frontiers in Endocrinology, 2022)
A case of hypoglycemic coma caused by a giant borderline phyllodes tumour of the breast has been described. The patient, a 63-year-old female, was admitted with recurrent unconsciousness. And she had a giant breast tumor with decreased blood glucose, insulin, and C-peptide. The patient's hypoglycemia resolved rapidly after resection of the breast tumor. Pathological examination indicated a borderline phyllodes tumor of the breast, and immunohistochemistry suggested high expression of insulin-like growth factor-II (IGF2) in the tumor tissue. A literature review is also included to summarize the clinical characteristics of such patients and to serve as a unique resource for clinical diagnosis and treatment of similar cases.